2021
DOI: 10.1002/term.3233
|View full text |Cite
|
Sign up to set email alerts
|

Individualized tissue‐engineered veins as vascular grafts: A proof of concept study in pig

Abstract: Personalized tissue engineered vascular grafts are a promising advanced therapy medicinal product alternative to autologous or synthetic vascular grafts utilized in blood vessel bypass or replacement surgery. We hypothesized that an individualized tissue engineered vein (P‐TEV) would make the body recognize the transplanted blood vessel as autologous, decrease the risk of rejection and thereby avoid lifelong treatment with immune suppressant medication as is standard with allogenic organ transplantation. To in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…Tissue engineering, as a part of regenerative medicine, has great potential to cater the patients in need of reconstructive surgery and organ transplantation. As a model for this field, we recently showed that personalized tissue engineered veins could be transplanted to vena cava in a porcine model with efficient recellularization and full patency after one month [ 14 ]. On the artery side of vascular surgery, there is a great need of small-diameter blood vessels since the available grafts on the market suffer from problems with patency and infections [ 30 , [40] , [41] , [42] ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tissue engineering, as a part of regenerative medicine, has great potential to cater the patients in need of reconstructive surgery and organ transplantation. As a model for this field, we recently showed that personalized tissue engineered veins could be transplanted to vena cava in a porcine model with efficient recellularization and full patency after one month [ 14 ]. On the artery side of vascular surgery, there is a great need of small-diameter blood vessels since the available grafts on the market suffer from problems with patency and infections [ 30 , [40] , [41] , [42] ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown with ROTEM analysis that our reconditioned vascular grafts have better hemocompatibility with reduced activation of the intrinsic coagulation pathway, increased clotting and clot formation time and decreased alpha angle compared with native and decellularized scaffolds [ 14 ]. Recellularization of the personalized veins grafts, produced with the same procedure, starts as early as three days after transplantation and is very efficient to repopulate the tissue already two weeks post-surgery [ 14 ]. After 4 months in vivo , personalized tissue engineered arteries showed recellularization of the deeper layers of the vascular grafts ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With modifications, these and other perfusion systems specifically developed for ex vivo pig, sheep and human uterus perfusion [62][63][64][65], will likely prove to be of significant value for future whole uterus recellularization protocols. During this extended in vitro recellularization time, multiple cell types will need to be applied in sequence, including endothelial cells for the vasculature reconstruction [66,67].…”
Section: Current Obstacles and Future Perspectivesmentioning
confidence: 99%